2020
DOI: 10.1016/j.ijepes.2019.105378
|View full text |Cite
|
Sign up to set email alerts
|

A smart community energy management scheme considering user dominated demand side response and P2P trading

Abstract: This paper proposed a Peer-to-Peer (P2P) local community energy pool and a User Dominated Demand Side Response (UDDSR) that can help energy sharing and reduce energy bills of smart community. The proposed UDDSR allows energy users within the community to submit flexible Demand Response (DR) bids to Community Energy Management Scheme (EMS) with flexible start time, stop time and response durations with regard to users' comfort zones for electric heating systems, electric vehicles and other home appliances, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 29 publications
0
78
0
Order By: Relevance
“…When comparing our results with existing literature, it is observed that Zhou et al (2020) explored the paradigm of user dominated DR and peer-to-peer trading on a local energy market of 50 households. Here, a PV installation of 3,2 kWp was used for the simulation.…”
Section: Evaluation Of the Results Of The Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…When comparing our results with existing literature, it is observed that Zhou et al (2020) explored the paradigm of user dominated DR and peer-to-peer trading on a local energy market of 50 households. Here, a PV installation of 3,2 kWp was used for the simulation.…”
Section: Evaluation Of the Results Of The Modelmentioning
confidence: 83%
“…With a penetration of 50% PV, which is similar to our case, an annual saving on the cost of electricity provision of 17,7% was achieved with only peer-to-peer trading. The increase in savings of the consumers through DR was not reported by Zhou et al (2020).…”
Section: Evaluation Of the Results Of The Modelmentioning
confidence: 90%
“…P2P electricity exchange models are attractive for both prosumers and customers, because prosumers have the opportunity to sell surplus electricity to peers at higher tariffs than the amounts they could sell back to the supplier, while consumers could buy local renewable electricity at lower tariffs [7][8][9]. P2P trading essentially turns passive customers into active market participants who participate in trading their available energy resources [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modern-day consumers have become prosumers by which they satisfy their own demand and with the surplus, they either give back to the grid or deliver to one or more peers. Consequently, local energy trading among peers subscribed to a common market framework is encouraged, leading to a P2P transactive environment [1] - [3]. To facilitate this framework, local energy networks incorporate bidirectional power flow and smart metering, information & communication technology, cyber-physical interaction, decentralized control [4] and trading platforms [5].…”
Section: Introductionmentioning
confidence: 99%